Season two: the kingdoms episode 14: Palestine the promise and & the Phoenician language - Yaacob, Solehah@Nik Najah Fadilah (2018)
Mitos budaya paling lama bertahan bangsa Yahudi adalah idea daripada 'tanah yang dijanjikan' atau `the promise land`. Penyebaran 'Palestin' sebagai 'tanah air Yahudi benar' berterusan hingga ke hari ini di dalam kajian biblical study dan menafikan sejarah purba Palestin itu sendiri. Menurut Keith W. Whitelam, ‘its concern with the broad themes of history, settlement, demography and economy was conceived to be an antidote to the standard histories of ancient Israel based upon the biblical traditions which have dominated biblical studies since the nineteenth century. Biblical studies never gave chance to ancient palestinians (= arabs) as the original settlers of the land’ Keith W. Whitelam (1996), the invention of ancient Israel, London: Routledge, p. 1.